Magnetic Control and Real‐Time Monitoring of Stem Cell Differentiation by the Ligand Nanoassembly. Issue 41 (13th September 2021) - Lee, Sungkyu; Kim, Myeong Soo; Patel, Kapil D.; Choi, Hyojun; Thangam, Ramar; Yoon, Jinho; Koo, Thomas Myeongseok; Jung, Hee Joon; Min, Sunhong; Bae, Gunhyu; Kim, Yuri; Han, Seong‐Beom; et al.
Abstract: Native extracellular matrix (ECM) exhibits dynamic change in the ligand position. Herein, the ECM‐emulating control and real‐time monitoring of stem cell differentiation are demonstrated by ligand nanoassembly. The density of gold nanoassembly presenting cell‐adhesive Arg‐Gly‐Asp (RGD) ligand on Fe3 O4 (magnetite) nanoparticle in nanostructures flexibly grafted to material is changed while keeping macroscale ligand density invariant. The ligand nanoassembly on the Fe3 O4 can be magnetically attracted to mediate rising and falling ligand movements via linker stretching and compression, respectively. High ligand nanoassembly density stimulates integrin ligation to activate the mechanosensing‐assisted stem cell differentiation, which is monitored via in situ real‐time electrochemical sensing. Magnetic control of rising and falling ligand movements hinders and promotes the adhesion‐mediated mechanotransduction and differentiation of stem cells, respectively. These rising and falling ligand states yield the difference in the farthest distance (≈34.6 nm) of the RGD from material surface, thereby dynamically mimicking static long and short flexible linkers, which hinder and promote cell adhesion, respectively. Design of cytocompatible ligand nanoassemblies can be made with combinations of dimensions, shapes, and biomimetic ligands for remotely regulating stem cells for offering novel methodologies to advance regenerative therapies. Abstract : The extracellular matrix (ECM)‐emulating control of ligand nanoassembly is reported. Magnetic control of increasing and decreasing vertical distance of the ligand nanoassembly from material surface hinders and promotes mechanotransduction‐mediated stem cell differentiation, respectively, in a ligand nanoassembly density manner, and it can be nontoxically and noninvasively monitored via in situ real‐time electrochemical sensing.